The official Stardew Valley cookbook - ConcernedApe (Video game designer); Novak, Ryan; Vu, Susan (Random House Worlds, 2024)
"Welcome to Stardew Valley, where each season brings a new crop of bountiful food to make for friends and family. From farm staples like veggies, fruit, milk, and eggs to foraged mushrooms and berries to fresh fish, there's always something delicious to put on the table. These 50 recipes are based on in-game meals and food, allowing you to cook and eat all your homegrown and fresh-caught ingredients in real life. The Official Stardew Valley Cookbook is organized by season and has recipes from your favorite characters, including the Queen of Sauce and Gus at the Stardrop Saloon. Written in collaboration with independent game creator ConcernedApe and packed with original illustrations and food photography, The Official Stardew Valley Cookbook helps you bring the Valley's incredible flavors to the dinner table, giving you the energy to take on the world." --